initiating the internationalization process of Vietnamese born global firms - Huynh, Thi (My University, 2014)
The degree of internationalization of the Vietnamese economy has been steadily increasing since the start of the Open policy in 1986. In this context, Vietnamese born global firms has been increasingly active in the international market. Understanding and following the internationalization process has become essential for these firms. Theoretically, the firm starts the internationalization process by analyzing the motivation, barriers, enabling factors for internationalization such as previous knowledge, social and business network, resource and capability, and international entrepreneurship. Based on the advantages and disadvantages analyzed, the firm continues the steps of opportunity identification, exploitation, and development. Lastly, the choice of target market and the entry mode to penetrate the chosen market are the last steps of the process. In the empirical part of the study, the qualitative and multiple – cased research method was conducted to examine and investigate the internationalization process of two Vietnamese born global firms in food manufacturing industry. Finding from the empirical part shows that the rapid internationalization of the firm is driven by the characteristic and the network of the founders. The global mindset of the founders is considered as the initiative of the internalization process of the firms. Besides, social and business network of the founders is the main factor enabling the firm to recognize and choose the potential market entry.
Keywords: Born global firm; internationalization process; network.; fi=Master's Degree Programme in International Business|